Battery positive plate and sodium ion battery
By applying an oxide coating that can absorb carbon dioxide on the surface of the positive electrode sheet of the sodium ion battery, the problems of battery inflation and safety risks at high voltages are solved, and the effect of reducing gas generation and protecting the performance of the battery cell is achieved.
Patent Information
- Application Number
- CN202420324864.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2034-02-21
AI Technical Summary
At high voltage, the positive electrode material of sodium ion battery produces a large amount of gas to the oxidation and decomposition of the electrolyte, resulting in safety risks such as cell flatulence, explosion and fire. At the same time, body-phase doping and surface coating methods will affect the conductivity network and dynamic performance of the cell.
A functional coating, particularly an oxide and/or peroxide coating, is preferably a calcium oxide coating, on the surface of the positive electrode sheet of the battery. The thickness and surface density of the coating are between 0.5 μm and 5 μm and 0.1 mg/cm2 to 15 mg/cm2, respectively, to absorb carbon dioxide and reduce the gas bloating problem of the battery cell.
By applying the functional coating, the gas generated by sodium ion batteries at high voltage is reduced, and the battery inflation and safety risks are reduced. At the same time, compared with the bulk-phase doping and surface coating methods, the impact on the cell performance is less.
Smart Images

Figure CN222600989U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of sodium ion batteries, and in particular to a positive electrode sheet of a battery. Meanwhile, the utility model also relates to a sodium ion battery provided with the positive electrode sheet of the battery. Background Art
[0002] At present, there are three main development directions for positive electrode materials of sodium-ion batteries: layered oxide positive electrode materials, polyanion positive electrode materials and Prussian white / blue positive electrode materials. Among them, layered oxide materials have been widely studied due to their advantages such as simple preparation, high gram capacity, high compaction density and adjustable operating voltage range. However, when using layered oxides as positive electrode materials for sodium batteries to develop high-voltage batteries, the battery cells usually face serious flatulence problems, which leads to rapid failure of battery cell performance and serious safety risks such as battery cell explosion and fire.
[0003] The gas production of sodium ion batteries under high voltage is mainly caused by the oxidation and decomposition of electrolyte by positive electrode materials. In order to solve the gas production problem of sodium ion batteries under high voltage, the existing technology often performs bulk doping and surface coating on layered oxide positive electrode materials. The purpose of bulk doping is to improve the bulk structural stability of positive electrode materials and reduce gas production by inhibiting transition metal dissolution and particle cyclic cracking.
[0004] Surface doping is to reduce the release of singlet oxygen on the surface of layered oxide materials and passivate the surface active sites to reduce the oxidative decomposition and gas production of the electrolyte. However, when reducing the gas production of the battery cell through bulk doping and surface coating methods, it often leads to the deterioration of the positive electrode conductive network, thereby increasing the positive electrode impedance, which is likely to have an adverse effect on the battery cell kinetic performance and cycle life. Utility Model Content
[0005] In view of this, the utility model aims to provide a battery positive electrode sheet to alleviate the flatulence problem of sodium ion batteries.
[0006] In order to achieve the above object, the technical solution of the utility model is implemented as follows:
[0007] A positive electrode sheet of a battery, comprising a sheet body and a coating portion coated on at least one side of the sheet body;
[0008] The coating portion includes a functional coating capable of absorbing carbon dioxide.
[0009] Furthermore, the functional coating is an oxide and / or peroxide coating capable of reacting with carbon dioxide.
[0010] Furthermore, the oxide coating is a calcium oxide coating.
[0011] Furthermore, the thickness of the functional coating is 0.5 μm to 5 μm.
[0012] Furthermore, the surface density of the functional coating is 0.1 mg / cm 2 ~15mg / cm 2 .
[0013] Furthermore, the pole piece body includes an aluminum foil and a positive electrode material layer coated on both sides of the aluminum foil.
[0014] Furthermore, the thickness of the aluminum foil is 10 μm to 16 μm.
[0015] Furthermore, the surface density of the positive electrode material layer is 3 mg / cm 2 ~30mg / cm 2 and / or,
[0016] The thickness of the pole piece body is 30 μm to 250 μm.
[0017] Compared with the prior art, the utility model has the following advantages:
[0018] The battery positive electrode plate described in the utility model is beneficial to reduce the gas generated during the recycling of the sodium ion battery by coating the surface of the electrode plate body with a functional coating capable of absorbing carbon dioxide, thereby alleviating the problem of battery flatulence and reducing the safety risk of using the sodium ion battery under high pressure. The functional coating is arranged on the surface of the electrode plate body, which has less effect on the performance of the battery cell compared with the form of bulk doping and surface coating.
[0019] In addition, by making the oxide coating a calcium oxide coating, the absorption effect of carbon dioxide is better, and it is easy to obtain and has a low cost.
[0020] In addition, by setting the thickness of the functional coating to 0.5 μm to 5 μm, it is possible to absorb carbon dioxide in the battery while reducing the impact on the electrochemical performance of the battery cell.
[0021] Another object of the present invention is to provide a sodium ion battery, comprising an electrode group consisting of a negative electrode sheet and the battery positive electrode sheet as described above.
[0022] Furthermore, the negative electrode sheet is a hard carbon negative electrode sheet.
[0023] The sodium ion battery described in the utility model has the same technical effects as the above-mentioned battery positive electrode sheet relative to the prior art, and will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation on the present invention. In the accompanying drawings:
[0025] Figure 1 It is a schematic structural diagram of a positive electrode sheet of a battery according to an embodiment of the utility model.
[0026] Description of reference numerals:
[0027] 1. Aluminum foil; 2. Positive electrode material layer; 3. Functional coating. DETAILED DESCRIPTION
[0028] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0029] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0030] In addition, in the description of the present invention, unless otherwise clearly defined, the terms "installation", "connection", "connection", and "connector" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood in combination with specific circumstances.
[0031] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments.
[0032] The present embodiment relates to a positive electrode sheet of a battery. In terms of overall structure, the positive electrode sheet of the battery comprises a plate body and a coating portion coated on at least one side of the plate body, wherein the coating portion comprises a functional coating 3 capable of absorbing carbon dioxide.
[0033] Since most of the gas generated by the oxidation and decomposition of the electrolyte by the positive electrode material is carbon dioxide, in this embodiment, by coating the surface of the pole piece body with a functional coating 3 that can absorb carbon dioxide, the gas generated during the cycle of the sodium ion battery can be reduced, thereby alleviating the problem of battery flatulence and reducing the safety risk of using sodium ion batteries under high pressure. The functional coating 3 is arranged on the surface of the pole piece body, which has less effect on the performance of the battery cell compared to bulk doping and surface coating.
[0034] As a preferred implementation method, Figure 1 As shown in , in this embodiment, both sides of the pole piece body are coated with a functional coating 3 to improve the absorption effect of carbon dioxide. Of course, in this embodiment, both sides of the pole piece body are coated with a functional coating 3, which is only a preferred embodiment. In addition, in other embodiments, the functional coating 3 can also be coated on only one side of the pole piece body.
[0035] Preferably, in this embodiment, the functional coating 3 is an oxide coating that can react with carbon dioxide, which is easy to manufacture and has low cost. Specifically, the oxide coating can be a calcium oxide coating. In this case, calcium oxide can react with carbon dioxide to produce calcium carbonate, and calcium carbonate will not be electrochemically decomposed, thereby effectively alleviating the problem of battery cell flatulence. In addition, calcium oxide is easy to obtain and has low cost.
[0036] Of course, the oxide coating may also be a coating made of other oxides, such as a magnesium oxide coating, a sodium oxide coating, and a potassium oxide coating. In addition, the functional coating 3 may also be a peroxide coating, such as a sodium peroxide coating. In addition, the functional coating 3 may also include oxides and peroxides at the same time, and the functional coating 3 may contain one or more oxides and peroxides at the same time, such as calcium oxide, magnesium oxide, sodium oxide, and sodium peroxide at the same time.
[0037] When making the functional coating 3, after selecting the type of oxide or peroxide, take a certain amount of oxide or peroxide, mix it with a surfactant, a binder and NMP (N-methylpyrrolidone) in a certain proportion in a homogenizer to form a uniform mixed slurry, and then use a gravure coater to apply the slurry to the surface of the electrode body.
[0038] As a preferred implementation, in this embodiment, the thickness of the functional coating 3 is 0.5 μm to 5 μm, and specifically can be 0.5 μm, 1 μm, 2 μm, 2.5 μm, 4 μm and 5 μm. By setting the thickness of the functional coating 3 within the above range, it is possible to absorb the carbon dioxide in the battery while reducing the impact on the electrochemical performance of the battery cell. In addition, the surface density of the functional coating 3 can be 0.1 mg / cm 2~15mg / cm 2 , which can be specifically 0.1mg / cm 2 , 5mg / cm 2 、10mg / cm 2 、15mg / cm 2 Such an arrangement facilitates ensuring the absorption effect of carbon dioxide while reducing the amount of the functional coating 3 and further reducing the impact on the electrochemical performance of the battery cell.
[0039] Preferably, in this embodiment, the electrode body includes an aluminum foil 1 and a positive electrode material layer 2 coated on both sides of the aluminum foil 1. It should be noted that when the positive electrode material layer 2 in this embodiment is produced, the sodium layered oxide positive electrode material (the positive electrode material chemical formula is Na1-xM1yM2zM3tM4sO2-δ, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤t≤1, 0≤s≤1, 0≤δ≤1. In the above chemical formula, M1, M2, M3, and M4 are all Li, Na, K, Mg, Ca, Sr, Ba, Al, Ga, In, Si, Ge, Sn, Pb, Sc, V, Cr, Mn, F e, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, La, Ce, Pr, Nd, Sm, Eu, Gd, Er, Tm, Yb, Lu, W, Pt or Au), a conductive agent (one or more of conductive carbon black, carbon nanotubes, acetylene black, Ketjen black, graphene, etc.), an adhesive and NMP (N-methylpyrrolidone) are uniformly mixed in a certain proportion and then slurried. After the slurrying is completed, it is coated on both sides of the aluminum foil 1 and dried.
[0040] In addition, in this embodiment, the thickness of the aluminum foil 1 is 10 μm to 16 μm, and specifically can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm and 16 μm. In addition, the surface density of the positive electrode material layer 2 can be preferably 3 mg / cm 2 ~30mg / cm 2 , so that the thickness of the electrode body is 30 μm to 250 μm. And the surface density of the positive electrode material layer 2 can be specifically 3 mg / cm 2 、15mg / cm 2 , 25mg / cm 2 、30mg / cm 2 The thickness of the pole piece body may be 3 μm, 150 μm, 200 μm, 250 μm, etc.
[0041] Of course, in this embodiment, the surface density of the positive electrode material layer 2 is set to 3 mg / cm 2 ~30mg / cm 2, making the thickness of the pole piece body 30μm to 250μm is only used as a preferred implementation. In addition, in other embodiments, the surface density of the positive electrode material layer 2 or the thickness of the pole piece body can also be set to other sizes.
[0042] The battery positive electrode plate of this embodiment is coated with a functional coating 3 capable of absorbing carbon dioxide on the surface of the electrode plate body, which can reduce the gas generated during the circulation of the sodium ion battery, thereby alleviating the problem of battery flatulence and reducing the safety risk of using the sodium ion battery under high pressure, with little effect on the electrochemical performance of the battery cell, simple production and low cost.
[0043] This embodiment also relates to a sodium ion battery, which includes an electrode group consisting of a negative electrode sheet and the above-mentioned positive electrode sheet. It should be noted that the positive electrode sheet and the negative electrode sheet can be made into an electrode group in a manner commonly used in the prior art, such as lamination.
[0044] In addition, the negative electrode sheet in this embodiment is preferably a hard carbon negative electrode sheet, which has a high gram capacity and obvious advantages in sodium storage capacity.
[0045] The sodium ion battery of this embodiment has the same technical effect as the above-mentioned battery positive electrode sheet relative to the prior art, and will not be described in detail here.
[0046] The use effect of the battery positive electrode sheet is described below in combination with further embodiments and related comparative examples.
[0047] Embodiment 1:
[0048] Positive electrode preparation:
[0049] In the laboratory, 77.72 g of PVDF (polyvinylidene fluoride) glue with a solid content of 6% dissolved in NMP (N-methylpyrrolidone), 30.7 g of NMP (N-methylpyrrolidone), 4.66 g of conductive carbon black, and 31.09 g of CNT (carbon nanotube) conductive liquid were weighed respectively, put into a 1L experimental positive electrode homogenizer and stirred for 30 minutes to obtain a uniformly mixed conductive glue.
[0050] Weigh 300g of sodium layered oxide positive electrode material, add it to the above conductive glue in batches, adjust the speed of the homogenizer to a reasonable value, and prepare the positive electrode slurry. After the homogenization is completed, the slurry is coated on a 12um aluminum foil 1 at a certain surface density. After the electrode is dried, roll it to a certain thickness to obtain the electrode body.
[0051] Weigh 30g of PVDF (polyvinylidene fluoride) glue solution with a solid content of 3% dissolved in NMP (N-methylpyrrolidone) into the homogenization tank of the degassing machine, add a surfactant (such as PVP, etc.) to the above PVDF (polyvinylidene fluoride) glue solution at a mass ratio of 1%, and stir it thoroughly to fully dissolve the surfactant. After the surfactant is completely dissolved, weigh a certain amount of calcium oxide powder and add it to the above solution and stir it to obtain a homogeneous and evenly dispersed calcium oxide suspension solution.
[0052] The suspension is evenly coated on the electrode body, and after drying and cutting into a certain size, the final positive electrode is obtained.
[0053] The negative electrode is made of hard carbon material, the diaphragm is a PE diaphragm, and the electrolyte is NaPF6 (sodium hexafluorophosphate, the concentration in the electrolyte is 1 mol / L) dissolved in a mixture of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1. It is assembled into a battery cell with a positive electrode sheet coated with a functional coating 3 on the surface, and its gas production and electrochemical performance under high voltage are tested.
[0054] Comparative Example 1:
[0055] In the laboratory, 77.72 g of PVDF (polyvinylidene fluoride) glue with a solid content of 6% dissolved in NMP (N-methylpyrrolidone), 30.7 g of NMP (N-methylpyrrolidone), 4.66 g of conductive carbon black, and 31.09 g of CNT (carbon nanotube) conductive liquid were weighed respectively, put into a 1L experimental positive electrode homogenizer and stirred for 30 minutes to obtain a uniformly mixed conductive glue.
[0056] Weigh 300g of sodium layered oxide positive electrode material, add it to the above conductive glue in batches, adjust the speed of the homogenizer to a reasonable value, and prepare the positive electrode slurry. After the homogenization is completed, the slurry is coated on a 12um aluminum foil 1 at a certain surface density. After the electrode sheet is dried, it is rolled to a certain thickness, and cut into a certain size to obtain a positive electrode sheet suitable for a soft-pack battery cell.
[0057] The negative electrode is made of hard carbon material, the diaphragm is a PE diaphragm, and the electrolyte is NaPF6 (the concentration in the electrolyte is 1 mol / L) dissolved in a mixture of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1. It is assembled into a battery cell with a positive electrode sheet coated with a functional coating 3 on the surface, and its gas production and electrochemical performance under high voltage are tested.
[0058] Embodiment 2:
[0059] In this embodiment, the functional coating 3 of the positive electrode sheet is a sodium oxide coating, and other conditions are exactly the same as those in Embodiment 1.
[0060] Embodiment 3:
[0061] In this embodiment, the functional coating 3 of the positive electrode sheet is a magnesium oxide coating, and other conditions are exactly the same as those in Embodiment 1.
[0062] Embodiment 4:
[0063] In this embodiment, the functional coating 3 of the positive electrode sheet is a calcium oxide coating, and the amount of calcium oxide in the calcium oxide coating is half of the amount of calcium oxide in the calcium oxide coating of Example 1. Other conditions are exactly the same as those of Example 1.
[0064] Embodiment 5:
[0065] In this embodiment, the functional coating 3 of the positive electrode sheet is a calcium oxide coating, and the amount of calcium oxide in the calcium oxide coating is twice the amount of calcium oxide in the calcium oxide coating of Example 1.
[0066] In each embodiment and comparative example, the type of positive electrode material, coating surface density, and compaction density used are the same, and only the type and amount of surface functional coating 3 are different. The capacity of the battery cells after capacity division is the same, which is 2.2Ah.
[0067] The sodium ion battery cell prepared as above was tested for 200 cycles at 25° C. to test its capacity retention rate and the actual inflation of the battery cell under different embodiments and comparative examples. The residual gas amount inside the battery cell after 200 cycles was accurately tested by the drainage method.
[0068] The cell performance test conditions are: voltage window range 1.5 ~ 4.10V, charging current 0.5C, discharge current 1.0C. The test results are shown in Table 1.
[0069] Table 1
[0070]
[0071] It can be seen from Table 1 that by coating the surface of the pole piece with a functional coating, the flatulence of the battery cell can be reduced, and when the functional coating is a calcium oxide coating, the absorption effect of carbon dioxide is better.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode sheet for a battery, characterized in that: It includes a pole piece body and a coating portion coated on at least one side of the pole piece body; The coating portion includes a functional coating capable of absorbing carbon dioxide.
2. The positive electrode sheet of a battery according to claim 1, characterized in that: The functional coating is an oxide and / or peroxide coating capable of reacting with carbon dioxide.
3. The positive electrode sheet of a battery according to claim 2, characterized in that: The oxide coating is a calcium oxide coating.
4. The positive electrode sheet of a battery according to claim 2, characterized in that: The thickness of the functional coating is 0.5 μm to 5 μm.
5. The positive electrode sheet of a battery according to claim 2, characterized in that: The surface density of the functional coating is 0.1 mg / cm 2 ~15mg / cm 2 .
6. The positive electrode sheet of a battery according to claim 1, characterized in that: The pole piece body comprises an aluminum foil and a positive electrode material layer coated on both sides of the aluminum foil.
7. The positive electrode sheet of a battery according to claim 6, characterized in that: The thickness of the aluminum foil is 10 μm to 16 μm.
8. The positive electrode sheet of a battery according to claim 6, characterized in that: The surface density of the positive electrode material layer is 3 mg / cm 2 ~30mg / cm 2 and / or, The thickness of the pole piece body is 30 μm to 250 μm.
9. A sodium ion battery, characterized in that: The invention comprises an electrode group consisting of a negative electrode sheet and a positive electrode sheet of a battery as claimed in any one of claims 1 to 6.
10. The sodium ion battery according to claim 9, characterized in that: The negative electrode sheet is a hard carbon negative electrode sheet.